2016
DOI: 10.18488/journal.9/2016.3.1/9.1.10.23
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Demography in Moderation the Influence of Nonverbal Communication to Patient’s Satisfaction

Abstract: Effective nonverbal communication affects patient satisfaction and also affects the optimal level of patient's healthiness. This is primarily caused by asymmetry information between doctor and patient since in most cases patients heavily rely on nonverbal communication as a tool to get information they need. Patient's sensitivity to the nonverbal communication is generally varied in according to their demography characteristics. This research is aimed at analyzing the effect of non-verbal communication to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Previous research shows that among the six nonverbal communication indicator variables that is the artifact, haptic, chronemics, proxemics, kinesics, and vocalic; the dominant variable influence is haptic. Besides haptic, another variable that influence patient satisfaction and desire to collaborate in the process of treatment as a result of satisfaction with the way physician communication is vocalic and kinemics (Sudirman, 2015b). Sudirman (2015a) found that nonverbal communication could significantly affect patient's satisfaction simultaneously.…”
mentioning
confidence: 99%
“…Previous research shows that among the six nonverbal communication indicator variables that is the artifact, haptic, chronemics, proxemics, kinesics, and vocalic; the dominant variable influence is haptic. Besides haptic, another variable that influence patient satisfaction and desire to collaborate in the process of treatment as a result of satisfaction with the way physician communication is vocalic and kinemics (Sudirman, 2015b). Sudirman (2015a) found that nonverbal communication could significantly affect patient's satisfaction simultaneously.…”
mentioning
confidence: 99%